Phenotyping the right heart according to left ventricular geometry patterns in severe HFrEF. (14th October 2021) - Casati, M; Bursi, F; Mondellini, G.M; Santangelo, G; Giustiniani, A; Massironi, L; Tarricone, D.G.F; Carugo, S; Guazzi, M
Abstract: Background: Right ventricular (RV) failure significantly impact on heart failure with reduced ejection fraction (HFrEF) prognosis. How and whether specific functional and geometrical phenotypes of the RV function adapt and combined with left ventricular (LV) geometry is unknown. Purpose: To test the RV function across LV geometrical patterns looking at respective prognostic roles. Methods: We retrospectively examined a population of patients homogenously diagnosed with chronic HFrEF (defined as LV ejection fraction (EF) less than 35%) and treated with optimal therapy (OT) and all implanted with ICD for primary prevention of sudden cardiac death. Patients were categorized by echocardiography according to remodeling pattern based on left ventricular mass index and relative wall thickness into four groups: normal geometry (NG), concentric remodeling (CR), concentric hypertrophy (CH) and eccentric hypertrophy (EH). RV parameters were: tricuspid annulus plane systolic excursion (TAPSE), TAPSE/pulmonary artery pressures (PAPs), RV basal diameter and fractional area change (FAC). Outcome variable was all-cause mortality, assessed with multivariable Cox proportional hazard (PH) models. Results: Among 193 patients (age 66±11 years, 81% men, 74% with ischemic etiology of HF and EF 28±5%) 21% had NG, 3% had CR, 8% had CH, and 68% had EH. Distribution of RV echo parameters across LV remodeling groups is shown in table 1. Over a median follow-up time of 4 (1.9 – 6.1) years, 65 deaths occurred. In multivariable Cox PH models adjusted for age, LVEF, ischemic etiology and LV geometry, TAPSE, TAPSE/PAPs, RV basal diameter and FAC strongly and independently predicted the outcome variable [HR 0.92 (95% C.I. 0.86–0.98), HR 0.08 (95% C.I. 0.01–0.57), HR 1.87 (95% C.I. 1.29–2.71), HR 0.97 (95% C.I. 0.95–1.00), respectively all p-value <0.05]. Conclusion: In a homogeneously defined population of severe HFrEF outpatients receiving OT, the majority showed EH remodeling pattern, which did not predict the primary outcome. LV geometry did not further stratify patients in this high risk group. Conversely, RV dysfunction proved to be a strong predictor of mortality, independently of age, LV function and etiology of HF, regardless LV morphology. Funding Acknowledgement: Type of funding sources: None.